The common school awakening: religion and the transatlantic roots of American public education - Komline, David (Oxford scholarship online, 2020)
'The Common School Awakening' offers a new narrative that counters previous conceptions about the rise of public schools in America. In this text, David Komline tells how Christian reformers played a defining role in the movement to systematize and professionalize American education in the first half of the nineteenth century.